An Invitation to Encourage Due Consideration for the Survivability of Rescued Businesses in the Business Rescue System of England and Wales. Issue 2 (20th June 2017) - Adebola, Bolanle
Abstract: Rescue seeks to preserve the going concern in a financially distressed but potentially viable business. It aims, on one hand, to maximise the value in distressed businesses and, on the other, to give potentially viable but distressed businesses the opportunity of a second chance. In England and Wales, the main rescue process is structured to strive for the former but pays relatively little attention to the latter. The mechanisms that have been introduced to maximise the prospects of the achieving a going concern sale have been associated with the subsequent failure of the rescued business. It appears, therefore, that there is a discord between value maximisation and the survivability of rescued businesses. In 2015, the Graham Review sought to alleviate this discord by proposing the voluntary independent viability report and viability statement. While this article agrees with the reforms to the extent that they encourage due consideration for the future survival of rescued businesses, it argues that the requirements ought to be mandatory and that the buyer should be required to demonstrate that the amount of leverage carried forward and the time span for repayment are calculated with due consideration for the earning capacity of the rescued business and its own operational needs. Copyright © 2017 INSOL International and John Wiley & Sons, Ltd